The Incredibles - Bird, Brad.; Nelson, Craig T.; Disney (Firm).; Viva Video Inc. (Firm). ([Burbank Walt Disney Studios Home Entertainment Distributed by Viva Video Inc., 2005)
Bob was one of the world's greatest superheroes fifteen years ago; now he's an insurance adjuster, living in the suburbs. Wanting to get back into action, he gets his chance when a mysterious call summons him to an island for a top-secret assignment.
Title from container.
Originally released as a motion picture in 2004.
Directors of photography, Andrew Jimenez, Patrick Lin, Janet Lucroy ; animation, Brett Coderre ... [et al.] ; art director, Ralph Eggleston ; editor, Stephen Schaffer ; music, Michael Giacchino ; production designer, Lou Romano ; visual effects, Mach Tony Kobayashi ; produced by John Walker ; written by Brad Bird ; directed by Brad Bird.
Voices: Craig T. Nelson, Holly Hunter, Samuel L. Jackson, Jason Lee, Spencer Fox, Sarah Vowell, Elizabeth Peña, Bud Luckey, Brad Bird, Kimberly Adair Clark, John Ratzenberger.
MPAA rating: PG; for some material that may not be suitable for children; Canadian Home Video rating: G.
Dolby Digital 5.1 ; requires Blu-ray player.
Keywords: Criminal investigation -- Drama; Criminal behavior -- Drama; Summons -- Drama